Penyusunan Peta Desa Digital Desa Wanasaba Daya Menggunakan Sistem Informasi Geografis (ArcGIS) - Suhartini; Indra Gunawan; Hamzan Ahmadi (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The preparation of a digital village map is one form of utilizing information technology to support regional data management and development planning at the village level. Wanasaba Daya Village, located in Wanasaba District, East Lombok Regency, requires geographic data that are presented systematically and easily understood. So far, information related to administrative boundaries, road networks, settlements, and public facilities has not been fully documented in an integrated digital map. This study aims to develop a digital village map of Wanasaba Daya Village by utilizing a Geographic Information System (GIS) using ArcGIS software. The method applied is descriptive, with secondary data collection obtained from online sources, particularly the LapakGIS website, and adjustments based on field observations. Spatial data were processed and presented in several layers representing the main elements of the village area. The results indicate that the resulting digital village map is able to present geographic information in a more structured and informative manner. This digital village map is expected to be utilized by the village government as a supporting medium for regional data management, development planning, and as part of efforts to digitalize village administration